Regulasi terhadap Penipuan Identitas: Studi Fenomena ‘Catfish’ pada Social Networking Sites (SNS) - Dewi, Novy Sartika Putri Sari; Irwansyah, Irwansyah (Jurnal Studi Komunikasi, 2021)
The development of Social Networking Sites have affected the users. One phenomena is identity deception, widely known as 'catfish.’ Catfish appears because users can choose their own identities on social networking sites. Users may choose an identity that is considered ideal identity, even though it does not reflect the reality. In this situation, identity is being constructed and used to achieve something. This can be a threat for social networking sites users because it can be considered an infringement in the use of social networking sites. This study discuss the regulation made by the Indonesian government to deal with the threat of catfish as a form of identity deception. The research method used was the qualitative method.